The Internet, Shanghaiese Novel, and the Literary Memory of 'Blossoms' - Bingbing Shi (Writing Chinese: A Journal of Contemporary Sinophone Literature)
The advent of the internet has significantly impacted Sinophone literature. However, when discussing the relationship between the internet and literature, most scholars focus on genre fiction, whereas Jin Yucheng’s (金宇澄, 1952-) novel Blossoms (繁花) stands as an exception to this paradigm despite being first posted online. Focusing on the societal conditions and human relationships in Shanghai during both the 1960s and 1990s, the novel Blossoms was recognised as a literary classic by officials, academics, and general readers, and was adapted into a TV drama by Hong Kong director Wong Kar-wai (王家卫,1958-) in 2024. This article uses Blossoms as an example to explore how the internet has influenced literary creation, especially in creating a new genre and style of Shanghaiese novels (沪语小说). Combing textual analysis and memory studies, this article also shows that the internet has transformed literature into a digital memory space, allowing readers to actively participate in reading, discussing, and posting. The novel Blossoms in digital age has become a memory space for Shanghai nostalgia which resonates with the cultural symptoms in contemporary China.